Broadcasting achievements: Social media practices of Swedish parties in-between elections through the lens of direct representation. (1st June 2020) - Svensson, Jakob; Russmann, Uta; Cezayirlioğlu, Andaç Baran
Inspired by Coleman's call for a more 'direct representation', we address two neglected issues within the field of social media and political communication. We study a non-election period in Sweden (two randomly selected weeks in early 2016) and conduct a cross-platform comparison. The article is based on content analyses of the four prominent social media platforms: Facebook, Instagram, YouTube and Twitter. We seek to answer the following questions: do parties use social media platforms in-between elections? If so, for what purposes? Do parties use social media to interact in a direct manner with citizens? We focus on three different Swedish parties: the Social Democrats (incumbent), the Feminist Initiative (underdog) and the Sweden Democrats (populist right-wing). Our findings suggest a bleak direct representation in-between elections. Parties are more active on social media platforms during election campaigns. Twitter is the preferred platform, especially by the incumbent party for broadcasting achievements.